Little Larry goes to school : the true story of a timid chimpanzee who learned to reach new heights - Ellis, Gerry; Hess, Mary Rand (National Geographic kids., 2019)
Little Larry is an orphaned chimpanzee who doesn't know much about being a chimp. He has to go to his first day at the forest school to learn what chimp life is all about. Nestled in a primate sanctuary in Cameroon, Little Larry and his group of chimp friends go to the school each day to learn how to play, communicate, and climb like they would if they were chimps in the wild. The only trouble is, Little Larry doesn't want to learn how to climb. He's perfectly happy on the ground. Will the sanctuary keepers and other chimpanzees be able to teach Little Larry how to climb so he can graduate from forest school? This sweet story, with its beautiful photographs, explores the challenges of going to school, learning, and gaining confidence in yourself. This is a perfect read-aloud tale for children reluctant to try new things, preparing to enter kindergarten, or starting preschool for the very first time.